Embodying Emotional Dirty Work: A Messy Text of Patrolling the Border. Issue 3 (19th August 2014) - Rivera, Kendra Dyanne; Tracy, Sarah
Abstract : Purpose: "Dirty work" is an embodied, emotional activity, and may best be expressed through narrative thick description. In this essay we employ creative analytic techniques through a "messy text" for better understanding the tacit knowledge and emotionality of dirty work and dirty research. The vignettes, based upon ethnographic fieldwork with U.S. Border Patrol agents, viscerally reveal the embodied emotions of dirty work and doing dirty research. Design/methodology/approach: The research draws on a two and a half year ethnography of the U.S. Border Patrol in which the first author engaged in participant observation, shadowing, and interviews. Based upon the iterative data analysis and narrative writing techniques using verbatim quotations and field data, the essay provides a series of vignettes that explore the multi-faceted feelings of dirty work. Findings: Tacit knowledge about dirty work is unmasked and known through experiences of the body as well as emotional reactions to the scene. A table listing the emotions that emerged in these stories supplements the narrative text. The analysis shows how communication about emotions provides a sense-making tool that, in turn, elucidates both the challenges and the potential highlights of doing dirty work. In particular, findings suggest that emotional ambiguity the "moral emotions" of guilt and shame may serve as sense-making tools that can help in ethical decision-making and a re-framing of challenging situations. Originality/value: A field immersion alongside dirty workers, coupled with a creative writing approach, provides access to the fleeting, embodied, and fragmented nature of tacit knowledge—answering the questions of what dirty work feels like. The essay provides a behind the scenes exploration of U.S. Border Patrol agents—a profession that is alternately stigmatized or hidden from public view. Finally, the piece provides a self-reflexive account of the messy realities of conducting "dirty research" in a way that is open ended and embodied.